The effect of Hydrogen-rich „Truskavetska” bottled water on the swimming stress test in female rats - Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2024)
Background and aim. Despite the use of drinking hydrogen rich water both in clinical and sports medicine, further research into the mechanisms of its beneficial effect remains relevant. We found that both Naftussya bioactive water per se and combined balneotherapy have an ambiguous effect on physical performance. It was also found that the preventive use of “Truskavetska” bottled water, the chemical composition of which is somewhat similar to that of Naftussya bioactive water, has both similar and different effects on the post-stress parameters of rats. We set ourselves the goal of finding out the possibility of correcting the effect of "Truskavetska" bottled water on the post-stressor state of the neuro-endocrine-immune complex, as well as the endurance of rats by enriching it with hydrogen. Material and methods. The experiment is at 26 female Wistar rats purposefully divided into three homogeneous (according to the swimming test and HRV parameters) groups. 5 animals remained intact with free access to regular daily water. Rats of the control group (n=4) for 7 days loaded through a tube with “Truskavetska” bottled table water (2 mL once), while the animals of main group (n=17) received the same water, but enriched with Hydrogen. After completing the preconditioning course, a repeated swimming stress test was performed. The next day after stressing, a number of parameters of the neuro-endocrine-immune complex and metabolism were recorded. Results. Hydrogen rich water (HRW) minimizes the post-stressor increase in sympathetic tone and adrenal mass, and prevents the increase in catecholamines and corticosterone as well as plasma cells in the blood and rod-shaped neutrophils in the spleen. On the other hand, HRW prevents a post-stressor decrease in the intensity of macrophage phagocytosis and the bactericidal capacity of blood microphages, the content of lymphoblasts in the thymus, the activity of both antioxidant enzymes and vagal tone, and also minimizes the decrease in the content of eosinophils in the blood, non-alpha-lipoprotein cholesterol in the serum, and the mass of the spleen, in addition, the reduced content of plasma cells in the spleen reverses to an excess. Finally, the non-stress-responsive parameters of the control animals: the activity of AlT, CPhK, AsT and diene conjugates of the serum, the content of reticulocytes and Hassal’s bodies in the thymus - under the influence of HRW increase to one degree or another. Importantly, this also applies to the duration of swimming until exhaustion. A strong canonical correlation was found between the activity of antioxidant enzymes, on the one hand, and metabolic-endocrine (R=0.959) and immune (R=0.959) sets, on the other hand. Conclusion. Enrichment of "Truskavetska" bottled table water with hydrogen generally has a favorable effect on its stress-limiting and actotropic capacity, associated with antioxidant activity.